Influence of Maternal Filariasis on Childhood Infection and Immunity to Wuchereria bancrofti in Kenya - Malhotra, Indu (American Society for Microbiology, 2003)
To determine whether maternal filariasis influences the risk of infection by and immunity to Wuchereria bancrofti in children, we performed a cross-sectional study in an area of Kenya where filariasis is endemic. Residents of 211 households were enrolled; 376 parents and 938 of their offspring between the ages of 2 and 17 years were examined for filarial infection status as determined by blood-borne microfilariae and filarial antigenemia. Children of infected mothers had a three- to fourfold increased risk of filarial infection, as ascertained by circulating filarial antigen, relative to children of uninfected mothers (P < 0.001). Paternal infection did not correlate with childhood infection status, indicating a specific maternal effect. Peripheral blood mononuclear cells from children of filaria-infected mothers (n = 33) had higher levels of constitutive interleukin-5 (IL-5) and IL-10, increased microfilarial antigen-specific IL-5 production, and diminished microfilarial antigen-driven lymphocyte proliferation than cells from children of uninfected mothers (n = 46; P < 0.05). In contrast, there were no differences between the two groups in adult worm antigen-driven gamma interferon, IL-2, IL-4, IL-5, and IL-10 production and lymphocyte proliferation. These data indicate that maternal filarial infection increases childhood susceptibility to W. bancrofti and skews filaria-specific immunity toward a Th2-type cytokine response. The results support the notion that in utero exposure to filarial antigens affects the natural history of filariasis during childhood.